Hybrid micro‐grid operation characterisation based on stability and adherence to grid codes. Issue 3 (1st March 2014) - Syed, Mazheruddin Hussain; Zeineldin, Hatem Hussein; El Moursi, Mohamed Shawky
Abstract : Hybrid micro‐grids are one of the most viable solutions to the present day problem of integration of renewable energy into existing power systems. With various options available for implementation of hybrid micro‐grids, the stability of such systems has to be ensured before they can be implemented. Further, conventional micro‐grid operational studies do not take into consideration the constraints set by the grid codes. This study analyses three types of interconnections, possible for implementation of hybrid micro‐grids, taking into consideration the transient stability and grid code constraints. The hybrid micro‐grid considered comprises a synchronous diesel generator and an inverter‐based distributed generation. The results and analysis are conducted by time‐domain simulations using MATLAB/Simulink software. The results provide the actual operational limits of possible micro‐grid interconnections under the set of given constraints.